The Effect of Planting Media Composition and Liquid Organic Fertilizer Concentration of Maja Fruit on the Growth and Yield of White Oyster Mushrooms (Pleurotus Ostreatus) - Romdhon, Mochammad Syihab; Setiyono, Setiyono; Slameto, Slameto; Dewi, Nilasari; Arum, Ayu Puspita; Meliala, Susan Barbara Patricia Sembiring; Nisak, Fauziatun; Savitri, Dyah Ayu (International Journal on Food, Agriculture and Natural Resources, 2025)
Oyster mushroom (Pleurotus ostreatus) is a popular mushroom in Indonesia, with several factors affecting its yield, including seed quality, cultivation methods, and environmental conditions. The choice of planting media is crucial, as it must provide essential nutrients. Common media include straw and coffee husks, with the addition of liquid organic fertilizer (LOF) enhancing productivity. Maja fruit is particularly beneficial due to its NPK content, supporting mushroom growth. This research, conducted from February to May 2024 in Klungkung Village, Jember Regency, employed a completely randomized design (CRD) with three replications. The study tested media compositions—100% sawdust (M1), 75% sawdust and 25% straw (M2), and 75% sawdust and 25% coffee husk (M3)—alongside varying LOF concentrations: no LOF (P0), 75 ml/liter (P1), 150 ml/liter (P2), and 225 ml/liter (P3). Results indicated that the interaction between LOF concentration and media composition significantly affected the total number and weight of fruiting bodies. The best combination was P1M2 (75 ml LOF/liter with 75% sawdust + 25% straw). Media composition significantly influenced the number and weight of fruiting bodies, with M3 (75% sawdust + 25% coffee skin) recommended as the optimal choice. LOF concentration notably impacted total fruit body weight, while other parameters showed no significant differences.